In Vivo Inhibition of MicroRNA-326 in a NOD.H-2h4 Mouse Model of Autoimmune Thyroiditis - Zhao, Na; Wang, Zhenzhen; Cui, Xuejiao; Wang, Shuo; Fan, Chenling; Li, Yushu; Shan, Zhongyan; Teng, Weiping (Frontiers in Immunology, 2021)
Background: Previous studies reported that various miRNAs participate in autoimmune diseases, but the potential regulatory mechanism of miRNAs in autoimmune thyroiditis (AIT) needs further exploration. Objective: This study aimed to further verify that miR-326 contributes to AIT by regulating Th17/Treg balance through Ets-1 using lentiviral gene delivery through tail vein and thyroid injection in NOD.H-2h4 mice. Materials and methods: Five-week-old NOD.H-2h4 mice were divided randomly into tail vein and thyroid injection groups, and each received either mmu-miR-326 sponge (LV-sponge) or lentiviral vector control. Mice were divided for tail vein injection: the therapeutic LV-ctrl, therapeutic LV-sponge, prophylactic LV-ctrl and prophylactic LV-sponge groups. The control group was fed high-iodine water without vein injection. The thyroid infiltration of lymphocytes and serum TgAb value were investigated by thyroid haematoxylin and eosin (HE) staining and ELISA, respectively. Ets-1 and lymphocyte counts were measured by RT-PCR, western blotting and flow cytometry. The thyroid CD4+IL-17a+ cells and CD4+Ets-1+ cells were detected by immunofluorescence, and the serum cytokines were tested by ELISA. Results: In the tail vein injection groups, the thyroid inflammatory score and serum TgAb titre were significantly lower in the LV-sponge groups than the control and LV-ctrl groups while Ets-1 protein expression in mouse spleens was increased in the LV-sponge groups. Moreover, Th17/Treg ratio declined in the LV-sponge group and decreased significantly in the prophylactic LV-sponge group (P=0.036) tested by flow cytometry. Immunofluorescence showed that, in LV-sponge groups, CD4+IL-17a+ cells were decreased significantly (P=0.001), while CD4+Ets-1+ cells were increased significantly in the LV-sponge group(P=0.029). The serum IL-17/IL-10 was decreased significantly in LV-sponge group (P<0.05). In the thyroid injection groups, the thyroid inflammatory score and serum TgAb titre in the LV-sponge group decreased significantly compared with those in the LV-ctrl group (P<0.05). In addition, in LV-sponge groups, CD4+IL-17a+ cells were decreased, while CD4+Ets-1+ cells were increased significantly in the inhibition group evaluated by immunofluorescence. Moreover, tail vein injection of LV-sponge resulted in much lower TgAb levels in thyroiditis compared with thyroid injection. Conclusion: MiR-326 targeted therapy may be a promising approach for AIT. In addition, tail vein injection may achieve a better intervention effect than thyroid injection.